SOIL CONTENT OF SOME OXIDES AS A FUNCTION OF THE DEVELOPMENT IN NINAVAH GOVERNORATE / NORTH IRAQ - Qahtan D. Al-Khafagi; Aiad A. Al-Dulaimi; Ammar S. Esmael (Tikrit Journal of Pure Science)
The objective of this study was soil development by using some weathering parameters, soil samples were selected from four different locations in Ninavah Governorate (Al-Hadher, Al-Qayarah, Hamam al-alil, Tallafer, Faidah). The studied areas were selected according the variation of environmental conditions and climate. Chemical analysis was conducted using (XRF) Technique. Results of XRF Analysis also showed a clear increasing in immobile oxides of (SiO2, Fe2O3 and Al2O3) and trace (rare) elements (ZrO, MnO and TiO2) in Faidah soil and gradually decreased in Tallafer, Hamam al-alil, Al-Qayarah and reach its lowest levels in Al-Hadher soil. However the mobile oxides of (CaO) and the loss in ignition was increased in Al-Hadher soil and gradually decreased in Al-Qayarah, Hamam al-alil, Tallafer and reach its lowest levels in Faidah soil. Calculation of weathering indices has been done such as modified weathering potential index (MWPI), plagioclase index of alteration (PIA), weathering ratio (WR), bases / alumina (B/A), and weathering index (WI-1), (WI-2). Results of weathering indices included that the highest levels of weathering levels was found in Faidah soil (High Average rainfall) and the lowest weathering levels in Al-Hadher soil (Low Average rainfall ).